Estrellados - DeAlberich, Salvador; Sedgwick, Edward; Smith, Leonard; Keaton, Buster; Torres, Raquel; Alvarado, Don (Warner Archive Collection, 2014)
And speaking of Latin, as an added bonus, "Free and Easy" is now paired with its Spanish-language version "Estrellados". Rarely seen since its initial overseas release, "Estrellados" is a prime example of the once customary practice of "parallel production" that helped Hollywood market their fare overseas during the silent-to-sound transition. It's a full alternative version of the film, shot simultaneously with "Free and Easy" starring Buster and a Spanish-speaking cast. ¡Viva la Comedia! [Cover]